please answer this question.
Attachments:
![](https://hi-static.z-dn.net/files/dda/30dd7ac0c0abba6400a75051dc191e7f.jpg)
Answers
Answered by
13
Answer:
x² + x - 2
Step-by-step explanation:
Let α and β be the zeroes of the required polynomial.
♦ α = 1, β = - 2 (given)
• Sum of zeroes = α + β
→ (1) + (- 2)
→ 1 - 2
→ - 1
• Product of zeroes = αβ
→ (1)(- 2)
→ - 2
The required polynomial is :
→ p(x) = k [ x² - (α + β)x + αβ ]
- Putting known values.
→ p(x) = k [ x² - (- 1)x + (- 2) ]
→ p(x) = k [ x² + x - 2 ]
- Putting k = 1.
→ p(x) = x² + x - 2
Hence, the required polynomial is x² + x - 2.
Similar questions